Impression Management In Building Personal Branding Marco Randy - Dimas Rahmatulah,; Manik Sunuantari,; Tamara Klicek, (INJECT (Interdisciplinary Journal of Communication), 2025)
Public figures employ various strategies to elevate their popularity and cultivate a specific public image. A key tactic is effective impression management. Through strategic impression management, individuals can optimize the results of their personal branding endeavors. Marco Randy, a prominent figure in the entertainment industry as an influencer, host, and radio personality, exemplifies this concept. He has successfully crafted a distinctive personal brand that sets him apart from his peers.This qualitative study, grounded in theories of impression management and personal branding, is based on in-depth interviews and observations. The research findings reveal a dichotomy in Marco Randy's personality. While he presents a public persona that is engaging and extroverted, his private self often exhibits introverted tendencies. This duality becomes apparent when he interacts with large crowds, as he may experience energy depletion and seek solitude afterward. Despite this, he is widely perceived as a friendly and approachable public figure, though he is selective about his interactions with unfamiliar individuals.